Socialization of the Bestee Ku Platform to BTPN Syariah Customers to Improve MSMEs in Seririt District, Bali - Setya Surya Wardhana; Renny Oktafia (IJCS: International Journal of Community Service, 2023)
Socializing a Bestee Ku application in the community empowerment program that has joined BTPN SYARIAH, where this application is very useful and useful in developing the business of customer mothers, in the Bestee Ku platform there is learning material about a business for small, medium, and above with the aim of increasing customer knowledge regarding the tips of customer mothers in doing business in the Seririt sub-district area. This research uses the ABCD (Asset Based Community Development) method, which is a concept of community empowerment by developing the Bestee Ku platform, because it is related to the progress of MSMEs for customer mothers who have businesses and join BTPN SYARIAH which specifically creates an application called Bestee Ku, with the existence of This Bestee Ku program is also related to student internships at BTPN SYARIAH, one of which is as a facilitator accompanying customers whose aim is to help develop the businesses of customer mothers, as well as always providing direction and motivation in business, each student also accompanies customer mothers for 1 month 4 times meetings and they help each other to improve the business of customers and students and also gain new experiences, insights, relationships and knowledge.